DESAIN RUANG KOMUNAL SEBAGAI UPAYA OPTIMALISASI LAHAN SEMPIT DI KAWASAN KAMPUNG RAWA JAKARTA PUSAT - Mustaram, Agnatasya Listianti; Jayanti, Theresia Budi; Darmady, Irene Syona; Agustin, Laura Tri (Jurnal Bakti Masyarakat Indonesia, 2024)
Housing in a small area with dense population often becomes an obstacle for the society to obtain proper facilities. As residents of a certain area, people often face challenges with limited shared space. In certain contexts, communal space is temporarily scattered along the streets. The location of Kampung Rawa was chosen as the venue for the PKM (Community Service) due to the condition of the area that is situated on a confined area and lacking communal space. This Community Service Activity (Kegiatan Pengabdian Kepada Masyarakat) is carried out in an effort to respond to the problems faced by the community, especially the residents of Kampung Rawa, through the application of architectural knowledge. Kampung Rawa, which is part of the Johar Baru District, Central Jakarta, is one of the most densely populated settlements in Jakarta and has even been referred to as one of the most densely populated in Southeast Asia. In 2021, the population density of the Johar Baru District reached 60,788 people/km², which inevitably contributes to the rise of various social issues. One of them is the lack of communal spaces for community interaction. The presence of active communal spaces is considered to be one of the solutions to urban problems and also serves as a place for interaction. In designing a good communal space, all aspects of society need to be considered so that it can benefit not only one group of people but various groups. One of the things that are needed to be done is to interact directly with the community of Kampung Rawa, to get to know them more deeply in terms of their activities, limitations, and other contextual needs. This PKM (Community Service Program) utilizes a qualitative approach along with a phased design method to develop spaces for community activities and communal areas. ABSTRAK Hunian di lahan sempit dengan kepadatan tinggi kerap menjadi kendala bagi masyarakat untuk mendapatkan kecukupan fasilitas yang memadai. Sebagai penghuni suatu wilayah, seringkali warga dipersoalkan dengan keterbatasan ruang untuk bersama. Dalam lingkup tertentu, ruang bersama terbatas berada pada jalan-jalan kecil yang sifatnya sementara. Lokasi Kampung Rawa terpilih sebagai lokasi pelaksanaan PKM mengingat kondisi kampung yang berada pada lahan sempit dan tidak memiliki ruang komunal. Kegiatan Pengabdian Kepada Masyarakat ini dilakukan dalam upaya menanggapi masalah yang masyarakat hadapi khususnya warga Kampung Rawa melalui penerapan ilmu-ilmu arsitektur. Kampung Rawa yang merupakan bagian dari Kecamatan Johar Baru, Jakarta Pusat yang merupakan salah satu pemukiman terpadat di Jakarta bahkan pernah disebut sebagai salah satu pemukiman terpadat di Asia Tenggara. Pada tahun 2021, kepadatan penduduk Kecamatan Johar Baru mencapai 60.788 jiwa/km² dan hal ini tentunya menimbulkan berbagai masalah sosial. Salah satu diantaranya adalah ketiadaan tempat ruang komunal untuk masyarakat berinteraksi. Keberadaan ruang komunal yang aktif dianggap menjadi salah satu solusi masalah perkotaan sekaligus menjadi tempat untuk berinteraksi. Dalam mendesain ruang komunal yang baik maka segala aspek dalam masyarakat perlu diperhatikan sehingga dapat memberikan manfaat tidak hanya terhadap satu golongan masyarakat tetapi berbagai golongan. Salah satu hal yang harus dilakukan adalah berinteraksi langsung dengan masyarakat Kampung Rawa, untuk mengenal mereka lebih dalam dari segi aktivitas, keterbatasan, dan kebutuhan-kebutuhan lainnya yang kontekstual. Metode yang digunakan pada PKM ini adalah metode kualitatif dan metode tahapan perancangan ruang untuk berkegiatan warga dan ruang komunal